Dynamics of Dissolved Oxygen in Relation to Saturation and Health of an Aquatic Body: A Case for Chilka Lagoon, India. (20th February 2014) - Prasad, B. S. R. V.; Srinivasu, P. D. N.; Varma, P. Sarada; Raman, A. V.; Ray, Santanu
Abstract : Dissolved oxygen (DO) is essential for an aquatic ecosystem since it controls the biological productivity. Here, we propose a unidimensional dynamic model for DO by incorporating biological (photosynthesis, respiration, and mineralization), physical (atmospheric reaeration) and chemical (nitrification) processes so characteristic of shallow coastal water bodies. The analytical study of the proposed model is focussed on supersaturation and undersaturation of oxygen in the water body. The controllability of the ecosystem health has also been investigated. Model results indicate that, while undersaturation of oxygen is largely governed by nitrification and Net Ecosystem Metabolism (NEM), the supersaturation is controlled by photosynthetic activity. The model results are corroborated with observed data collected from Chilka lagoon, India. Subsequently, a biogeochemical model to study the DO variations in Chilka lagoon has been constructed. The model is properly calibrated and validated with observed data. Two independent sets of data (2004-2005 and 2005-2006) were used for model calibration and validation and Chi-square tests supported its robustness (R 2 = 0.982 and 0.987;P < 0.05 ). The model was used to evaluate independently the influence of individual taxa (diatoms, microphytobenthos, and cyanophyceans) on DO variations. Simulations indicate the vital role of microphytobenthos in lagoon DO dynamics and the overall wellbeing.